2019
DOI: 10.11646/zootaxa.4647.1.19
|View full text |Cite
|
Sign up to set email alerts
|

The intertidal genus Indopacifica (Acari, Oribatida, Selenoribatidae): new species, juvenile morphology and distribution

Abstract: Two new intertidal oribatid mite species from the Indo-pacific region are described. Indopacifica iohanna sp. n. was found on the coasts of the Philippines and can be distinguished from its congeners by the lack of a ventral tooth on the claws. The larva and nymphs of this species show the same type of plication and setation typical for juveniles of other selenoribatid mites. Indopacifica mauritiana sp. n. was discovered on the coast of Mauritius and can be separated from its congeners by possessing only vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 538 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Immature stages of I. iohanna, I. taiyo and I. tyida show conformity in all characters except for the legs. Indodpacifica iohanna juveniles can be distinguished by the lack of proximoventral teeth on the claws (Resch et al 2019 ), a character that is present in the juveniles of the two other species. Indopacifica taiyo and I. tyida show slight differences in the development of leg setation (details are outlined in the respective remarks section), which would allow distinction at least in the deutonymphal stage.…”
Section: Discussionmentioning
confidence: 99%
“…Immature stages of I. iohanna, I. taiyo and I. tyida show conformity in all characters except for the legs. Indodpacifica iohanna juveniles can be distinguished by the lack of proximoventral teeth on the claws (Resch et al 2019 ), a character that is present in the juveniles of the two other species. Indopacifica taiyo and I. tyida show slight differences in the development of leg setation (details are outlined in the respective remarks section), which would allow distinction at least in the deutonymphal stage.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses were run for 20e −6 , 15e −6 , and 10e −6 generations for the concatenated, COI and 18S dataset, respectively. To ensure parameter convergence and stationarity of chains, split deviation frequencies lower than 0.01 were assured and effective sample sizes (ESS) were investigated in Tracer 1.6 (Rambaut et al, 2014) (available at http://beast.bio.ed.ac.uk/Tracer). The first 25% of obtained trees of the MrBayes run were discarded and the rest summarized in terms of a 50% majority rule consensus tree.…”
Section: Molecular Genetic Analysesmentioning
confidence: 99%
“…Thalassozetes tenuisetosus was recorded on the coast of India (Bayartogtokh & Chatterjee 2010) and although Talker et al (1981) reported the occurrence of an undetermined Thalassozetes species from the Philippines, these specimens were recently described as members of the selenoribatid genus Indopacifica (Resch et al 2019). Therefore T. tenuisetosus is the only representative of this genus known from the Indo-Pacific area.…”
Section: Introductionmentioning
confidence: 99%